Patterns and trends in research on external public debt management - Mila Razinkova; Tetiana Grynko; Natalia Nebaba; Rostislav Botvinov; Dmytro Pryimachenko (Public and Municipal Finance)
The text of this article has been corrected. Information about the changes is provided here http://dx.doi.org/10.21511/pmf.14(2).2025.08 This study undertakes a comprehensive bibliometric analysis of publications pertaining to the external public debt management system. The paper aims to study the evolution of scholarly discourse surrounding the external public debt management domain, highlighting contributions, methodologies, and collaborative networks within the field. The methodology encompasses a multivariate approach, incorporating extensive searches across the three major scientometric databases: Google Scholar (PoP), Scopus (in-built Scopus tools, SciVal), and Web of Science (in-built WoS instruments). The bibliometric analysis extends to contextual, evolutionary, and spatial dimensions, allowing for a comprehensive understanding of the identified clusters. The ensuing clusters serve as a roadmap, categorizing publications based on their contextual relevance, evolutionary trajectory, and spatial focus, which enhances the identification of key works in the field, facilitating a nuanced understanding of the current state of external public debt management research. The synthesis of findings from the content-contextual block emphasizes a primary orientation toward understanding the dynamic interplay between external public debt management and economic development. Furthermore, the contextual-temporal block identifies four distinct stages in the evolution of research focus, highlighting the shifting emphasis over time. A discernible pattern of heightened research activity in external public debt management across various countries in recent decades is revealed through spatiotemporal analysis. The interdisciplinary nature of this field is underscored by the dominance of economics, econometrics, finance, business, management, and accounting in dedicated research.